Mechanisms of Releasing Fixed Potassium as Available Nutrient for Plant Growth on Smectitic Soils - DEDI NUSYAMSI (Jurnal Sumberdaya Lahan, 2011)
Smectitic soils have considerable prospects to be developed into agricultural land. The distribution of these soils is quite large, i.e. more than 2.12 million ha (approximately 2:12 million of Vertisols as well as Alfisols and Inceptisols which have vertic subgroup). Smectite mineral contributed significantly to the amount of soil negative charge and controled soil buffering capacity and soil K maximum sorption. Top soil (0-20 cm) of smectitic soils are generally clay-textured, neutral to alkaline in soil reaction, moderate to high in potential K, low to high in exchangeable K, and moderate to high in cation exchange capacity. Although soil total K was high, but most of the soil K was in an unexchangeable form so that it was not immediately available to plants. While soil buffering capacity and maximum sorption on K were high. One important aspect in the management of soil K is the use of K contained in the soil. This method is quite effective, particularly for smectitic soils. The use of contained K in soil can be through the mechanism of release from unexchangeable soil K pool to exchangeable soil K pool as well as desorption from exchangeable soil K pool to soluble soil K pool. After both rection take place then, the plants will easily absorb K for their growth.